A serial system of multi-stage reverse electrodialysis stacks for hydrogen production. (1st January 2022) - Zhang, Youwen; Wu, Xi; Xu, Shiming; Leng, Qiang; Wang, Sixue
Highlights: A multi-stage RED stacks for hydrogen production was proposed and tested. Salinity gradient energy harvest efficiency was improved by the multi-stage system. Both the output power and hydrogen production were steadily operated. Hydrogen production rate and energy efficiency were dependent on the current. There exists a maximal energy conversion efficiency at the optimal feed velocity. Abstract: Salinity gradient energy is converted to hydrogen energy by integrating reverse electrodialysis (RED) and electrolysis of water to produce hydrogen. In this work, a serial system of multi-stage RED sacks is proposed to improve the energy efficiency and working performance of direct hydrogen production. The experimental results show that, compared with a single-stage system, the multi-stage RED stack system showed significant improvements in both hydrogen production and power output. Appropriately reducing the working current while increasing the number of RED stacks was beneficial to net power output and energy conversion. Total hydrogen production was almost unaffected when the number of RED stacks was large. Maximum energy conversion efficiency occurred at an optimal feed solution velocity. Under these conditions, the maximum net output power, total hydrogen production, and total energy-conversion efficiency were 2.06 W, 881.88 mL h −1, and 7.74%, respectively. The results are of relevance to investigation of the thermal-energy-driven reverse-electrodialysis heat engine for hydrogen production.